I trust my immunity more than your vaccines: “Appeal to nature” bias strongly predicts questionable health behaviors in the COVID-19 pandemic - Iris Žeželj; Marija Petrović; Anja Ivanović; Predrag Kurčubić (PLoS ONE, 2023)
Health care policies often rely on public cooperation, especially during a health crisis. However, a crisis is also a period of uncertainty and proliferation of health-related advice: while some people adhere to the official recommendations, others tend to avoid them and resort to non-evidence based, pseudoscientific practices. People prone to the latter are often the ones endorsing a set of epistemically suspect beliefs, with two being particularly relevant: conspiratorial pandemic-related beliefs, and the appeal to nature bias regarding COVID-19 (i.e., trusting natural immunity to fight the pandemic). These in turn are rooted in trust in different epistemic authorities, seen as mutually exclusive: trust in science and trust in the “wisdom of the common man”. Drawing from two nationally representative probability samples, we tested a model in which trust in science/wisdom of the common man predicted COVID-19 vaccination status (Study 1, N = 1001) or vaccination status alongside use of pseudoscientific health practices (Study 2, N = 1010), through COVID-19 conspiratorial beliefs and the appeal to nature bias regarding COVID-19. As expected, epistemically suspect beliefs were interrelated, related to vaccination status, and to both types of trust. Moreover, trust in science had both a direct and indirect effect on vaccination status through both types of epistemically suspect beliefs. Trust in the wisdom of the common man had only an indirect effect on vaccination status. Contrary to the way they are typically portrayed, the two types of trust were unrelated. These results were largely replicated in the second study, in which we added pseudoscientific practices as an outcome; trust in science and the wisdom of the common man contributed to their prediction only indirectly, through epistemically suspect beliefs. We offer recommendations on how to make use of different types of epistemic authorities and how to tackle unfounded beliefs in communication during a health crisis.